Anti Inflammatory and Wound Healing Potential of Liverwort Extract and Collagen-Transdermal Patch in Diabetic Rats - Ilmany, Pasha Zaki; Wiratara, Muhammad Rafi Althaf; Fatimah, Ratu (Nusantara Science and Technology Proceedings, 2025)
Patients with diabetes often experience impaired wound healing, which is associated with intense inflammation. Liverwort extract is rich in secondary metabolites with anti-inflammatory properties, while collagen is crucial for skin regeneration and wound healing. This study investigated the effect of a transdermal patch containing liverwort extract and collagen derived from tilapia bones on inflammation and wound healing in diabetic rats. A completely randomized design was used, consisting of eight groups in total: a normal control group (C) on a standard diet, a negative control group (NC) injected with alloxan at a dose of 120 mg/kg body weight, a positive control group (PC) injected with alloxan and treated with a transdermal patch containing an antibiotic, and five groups injected with alloxan and treated with transdermal patches containing different ratios of liverwort extract and collagen for 14 days. An analysis of variance was used for all data with 5% significance levels (p<0.05). The results showed that alloxan significantly increased blood sugar levels, confirming that the rats were in a diabetic condition. Wound healing was compared among the non-diabetic group, the diabetic group, and the diabetic-treated groups, with significant differences observed. The percentage of white blood cells observed in peripheral blood smear examinations was significantly lower in the diabetic-treated groups compared to the diabetic group, indicating substantial improvement. An increased number of white blood cells is associated with greater inflammation. The topical application of the liverwort and collagen transdermal patch reduced this effect. These findings indicate that the liverwort and collagen transdermal patch has the potential for reducing inflammation and promoting wound healing.